Fine mapping of trypanosomiasis resistance loci in murine advanced intercross lines - Iraqi, F.A.; Clapcott, S.J.; Kumari, P.; Haley, C.S.; Kemp, Stephen J.; Teale, A.J. (Springer, 2000)
We have previously reported the results of genome-wide searches in two murine F2 populations for QTLs that influence survival following Trypanosoma congolense infection. Three loci, Tir1, Tir2, and Tir3, were identified and mapped to mouse Chromosomes (Chrs) 17, 5, and 1 respectively, with confidence intervals (CIs) in the range 10–40 cM. The size of these CIs is to a large degree the consequence of limited numbers of recombination events in small chromosomal regions in F2 populations. A number of population designs have been proposed to increase recombination levels in crosses, one of which is the advanced intercross line (AIL). Here we report fine mapping of Tir1, Tir2, and Tir3 in G6 populations of two independent murine AILs created by crossing the C57BL/6J strain with the A/J and BALB/cJ strains, respectively. Data were analyzed by two methods that gave equally informative and similar results. The three QTLs were confirmed in the A/J × C57BL/6J AIL and in the combined data set, but Tir2 was apparently lost from the BALB/cJ × C57BL/6J AIL. The reduction in CIs for the Tir loci ranged from 2.5 to more than ten-fold in G6 populations by comparison with CIs obtained previously in the equivalent F2 generations. Mapping in the AILs also resolved the Tir3 locus into three trypanosomiasis resistance QTLs, revealing a degree of complexity not evident in extensive studies at the F2 level.